Peningkatan Ragam Genetik Cabai Rawit (Capsicum frustescen L) melalui Irradiasi Sinar Gamma Co-60 - Sukaya Sukaya; Sri Hartati (Caraka Tani: Journal of Sustainable Agriculture, 2005)
The objective of research was to asses the genetic variability of Hot Chili in order to increase genetic stock for plant breeding program. The research was conducted in A glass house of Plant Science Departement, Sebelas Maret University, irradiation of seed was done in BATAN Jakarta.The experimental design was Completely Randomized Design which consisted of two treatment, irradiation dosage and Chili  Varieties.The research conducted that dosages of irradiation affected the genetic variability of Chili. At the higher dosage of irradiation, there was A negative effect of gamma rays irradiation to the plant height, harvest age, number of red fruit, weight of red fruit and genetic variability. The heritability was high enough on all variables measured, except age flowering. Therefore, the genetic factor was more dominant on all variables, and for flowering age was more affected by environmental factor.